Associations Between Physical Activity, Mental Health Symptoms, and Physical Fitness among Sport-Specialized High School Students - Ismah, Siti Sayidah Qonita; Nurrachmad, Limpad (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
Regular physical activity (PA) has been associated with improved physical fitness (PF) and reduced symptoms of depression and anxiety among adolescents. However, evidence regarding these relationships among students enrolled in sport-specialized high school programs remains limited. This cross-sectional study examined the associations among PA, PF, and mental health symptoms (MHS) in 60 students (32 males and 28 females, aged 15–18 years) enrolled in sport-specialized classes at SMA Negeri 3 Rembang. PA was assessed using the International Physical Activity Questionnaire for Adolescents (IPAQ-A), PF was evaluated using the Tes Kebugaran Jasmani Indonesia (TKJI), and MHS were measured using the Depression Anxiety Stress Scales-21 (DASS-21). Because the data were not normally distributed, Spearman’s rank correlation analysis was performed. The analysis revealed a moderate positive correlation between PA and PF (rs = 0.503, p < 0.001), as well as significant negative correlations between PA and symptoms of depression (rs = –0.619, p < 0.001) and anxiety (rs = –0.505, p < 0.001). No significant correlation was found between PA and stress (rs = 0.006, p = 0.962). In addition, PF was not significantly associated with symptoms of depression (rs = –0.242, p = 0.063), anxiety (rs = –0.188, p = 0.151), or stress (rs = 0.158, p = 0.227). Overall, higher levels of PA were associated with better PF and lower symptoms of depression and anxiety, whereas no significant associations were observed between PA and stress or between PF and mental health outcomes. These findings underscore the importance of implementing structured school-based PA programs that promote both physical fitness and mental well-being among adolescents.